2017
DOI: 10.1016/j.ibmb.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Maternal provision of transformer-2 is required for female development and embryo viability in the wasp Nasonia vitripennis

Abstract: In insect sex determination a primary signal starts the genetic sex determination cascade that, in most insect orders, is subsequently transduced down the cascade by a transformer (tra) ortholog. Only a female-specifically spliced tra mRNA yields a functional TRA-protein that forms a complex with TRA2, encoded by a transformer-2 (tra2) ortholog, to act as a sex specific splicing regulator of the downstream transcription factors doublesex (dsx) and fruitless (fru). Here, we identify the tra2 ortholog of the hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 48 publications
4
41
0
Order By: Relevance
“…mellifera (Nissen et al ., ) and N . vitripennis (Geuverink et al ., ). A potential complex with the female‐specific TRA protein, as demonstrated in Drosophila melanogaster (Amrein et al ., ), can however only be formed at a later stage in development, when At‐tra F is actively transcribed in the zygote.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…mellifera (Nissen et al ., ) and N . vitripennis (Geuverink et al ., ). A potential complex with the female‐specific TRA protein, as demonstrated in Drosophila melanogaster (Amrein et al ., ), can however only be formed at a later stage in development, when At‐tra F is actively transcribed in the zygote.…”
Section: Discussionmentioning
confidence: 97%
“…Ap. mellifera (Nissen et al, 2012) and N. vitripennis (Geuverink et al, 2017) do possess alternative splice variants of tra2, but these are present in both sexes and across all life stages.…”
Section: No Alternative Splicing Of At-tra2mentioning
confidence: 99%
“…We performed protein–protein interaction assays in N. vitripennis to test the hypothetical TRA/TRA2 binding complex in Hymenoptera. Both tra and tra2 in N. vitripennis are required for the splicing of tra pre‐mRNA as well as dsx pre‐mRNA (Verhulst, Beukeboom, et al ., ; Geuverink et al ., ). In this study we demonstrated an interaction between TRA and TRA2 in N. vitripennis .…”
Section: Discussionmentioning
confidence: 97%
“…On the contrary, Btau‐tra2 was multi‐transcribed into three transcript variants instead of only one transcript as occurs with the tra2 genes of other tephritids and M. domestica (Salvemini et al, ; Sarno et al, ; Schetelig & Handler, ; Liu et al, ). To date, tra2 genes that are transcribed into multi‐transcripts have been found in other insect groups; for example, three transcripts were found to be produced in T. castaneum (Shukla & Palli, ), four in D. melanogaster , Aedes aegypti (Amrein et al, ; Liu et al, ) and N. vitripennis (Geuverink et al, ), six in Ap. mellifera and Bo.…”
Section: Discussionmentioning
confidence: 99%
“…In some insects, tra2 genes function both in determining sex and also in embryonic development such as in Ap. mellifera (Nissen et al, 2012), T. castaneum (Shukla & Palli, 2013) and Nasonia vitripennis (Geuverink et al, 2017).…”
Section: Introductionmentioning
confidence: 99%